La responsabilidad juridica del medico derivada de su practica profesional, y su incidencia en el derecho constitucional a la salud en la Republica del Ecuador. - Ortega Ortiz, Edison Arcesio (2014)
This thesis whose topic is " The Legal Liability of Medical derived from their practice, and their impact on the constitutional right to health in the Republic of Ecuador " whose objective was to propose a reform proposal by adding an article after the 199 to Health Code of the thesis plan and methodological issues and regulations established by Quevedo State Technical University, School of Law was made. The selection of reading material, let me make the theoretical framework while I did a historical, doctrinal and legal and jurisprudence , law comparative analysis of the subject matter and formulate hypotheses to guide field research , a study was conducted law in which it is determined the need for an article after 199 to Code of Health. Research based field surveys Doctors, lawyers in free practice, families of patients in government hospitals and interviews with Doctors and Lawyers in free practice, Quevedo Canton. The research design, the conclusions and recommendations, the proposal in which the preamble is done and the proposal is developed methodology is described.